Risky Business? : HIV Knowledge, Attitudes, and Behavior Among At-Risk Mobile Workers in Turkey - World Bank; Hacettepe Training, Research and Services Foundation; UN HIV/AIDS Joint Programme in Turkey; The Ministry of Health, Turkey (World Bank, Washington, DC, 2017)
This study focuses on, what is believed to be, a key client group of sex workers: mobile workers. While several studies have been conducted in Turkey on sex workers, little evidence exists on their clients, the demand side of the commercial sex market. Research from other countries has shown that mobile workers, who are often working-age males spending significant time away from home, are more likely to have multiple sexual partners and visit sex workers (World Bank, 2009; Kulis et al., 2009; Marck, 1999). The objective of this study is to determine the HIV knowledge, awareness, and behaviors among four mobile worker groups in Turkey that may have elevated risks for HIV infection and transmission: sailors, truck drivers, construction, and tourism workers. International transportation, construction, and tourism are some of the fastest growing sectors of Turkey's economy, and mobile workers in these sectors are believed to be one of the main HIV transmission routes for future infections (Tumer and Unal, 2006). It is important to note two caveats of this study. First, no biomarker data (e.g., HIV testing) was collected from these workers, so conclusions regarding HIV prevalence or concentration of the epidemic cannot be made. Second, the sample did not include other at-risk groups or the general population, so it is difficult to know whether the behaviors are more or less risky in other population groups. Where possible, comparisons with other studies or countries are presented, but there are likely important differences in sampling and methodology. The major contribution of this study, however, is that it characterizes the risk factors within the mobile worker population in Turkey.